Gender norms and agricultural innovation: Insights from six villages in Bangladesh - Aregu, Lemlem; Choudhury, Afrina; Rajaratnam, Surendran; Locke, Catherine; McDougall, Cynthia (Canadian Center of Science and Education, 2018)
This paper analyses how men and women in South West Bangladesh perceive gender norms to affect their ability to innovate, adopt, and benefit from new technologies in aquaculture, fisheries and agricultural systems. The qualitative findings from six villages in 2014 confirm that the engagement of women and men smallholders with agricultural innovation and its opportunities is gender-differentiated. The authors also explore further: how gender norms shape these differences; which gender norms are the most significant in the given context, when and for whom; and, finally, when and how some women and men are able to innovate in the context of these norms.